HUBUNGAN PERTUMBUHAN EKONOMI DAN PENGANGGURAN DI KALIMANTAN BARAT DENGAN PENDEKATAN KAUSALITAS GRANGER - B01111011, IRWANTO (Jurnal Pembangunan dan Pemerataan, 2016)
This study entitled "Relationship of Economic Growth and Unemployment In WestKalimantan With Granger Causality Approach". The purpose of this study was to examineand analyze the relationship between economic growth and unemployment in WestKalimantan with granger causality approach. This study was conducted to determine GrangerCausality test results were processed using a program or data processing applications Eviews6.0. The data used to support this research is secondary data, economic growth andunemployment data in West Kalimantan in 1984-2015 (time series) with a total of 32 years ofobservation data.This study shows one way causality relationship between the variables of economicgrowth and unemployment variables in West Kalimantan. It can be seen with the F-Statisticis smaller than the value of the F-table (0.01472) <(0.0417) and the probability is greater(0.9854)> (0:05) at the 5% significance level, so that the economic growth (Y) significantlyagainst unemployment (X) in West Kalimantan.Keywords: Economic Growth, Unemployment, Granger Causality Test.